Rainfall Pattern Change and Its Impact on Length of Growing Period - E. RUNTUNUWU; H. SYAHBUDDIN (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2007)
Information of global climate change impact on agriculture sector is needed for planning agricultural adaptation strategy. The objective of the study was to analyze the climate change in Indonesia, especially rainfall pattern change, and its impact on the length of growing period. The data used for analysis was collected during a period of 1879-2006 from Manonjaya station in Tasikmalaya District, West Java Province. The rainfall pattern was analyzed using Oldeman method, which is used to compute the length of growing period. Rainfall pattern was determined based on three types of rainfall characteristic, i.e., wet year, normal year, and dry year for each period of 1879-1910, 1911-1940, 1941-1970, and 1971-2006. The result of this research showed that the rainfall pattern had been changed over the past 128 years, with the following descriptions: on the wet year, the ‘A’ type of rainfall pattern has no changed, but the wet month has decreased about two months; on normal year, the rainfall pattern has changed from B1 to B2, and on dry year, it was from C2 to D3. The length of growing period was becoming shorter due to this changes. During wet year, three times cropping has changed to twice a year. During normal year, especially for enduring of the second growth period, the irrigation technology was necessary due to expand of water storage. During the dry year, due to the impact of dry spell, once crop a year will not be possible. The study provides insight into a strategy to adapt agriculture to climate change and to gain benefit of its change for suitable agriculture practices.